Fetal growth interacts with multilocus genetic score reflecting dopamine signaling capacity to predict spontaneous sugar intake in children. (1st January 2018) - Silveira, Patrícia P.; Pokhvisneva, Irina; Gaudreau, Hélène; Atkinson, Leslie; Fleming, Alison S.; Sokolowski, Marla B.; Steiner, Meir; Kennedy, James L.; Dubé, Laurette; Levitan, Robert D.; Meaney, Michael J.; ,
Abstract: Background: We have shown that intrauterine growth restriction (IUGR) leads to increased preference for palatable foods at different ages in both humans and rodents. In IUGR rodents, altered striatal dopamine signaling associates with a preference for palatable foods. Objectives: Our aim was to investigate if a multilocus genetic score reflecting dopamine-signaling capacity is differently associated with spontaneous palatable food intake in children according to the fetal growth status. Methods: 192 four-year old children from a community sample from Montreal and Hamilton, Canada, were classified according to birth weight and administered a snack test meal containing regular as well as palatable foods. Intrauterine growth restriction was based on the birth weight ratio below 0.85; children were genotyped for polymorphisms associated with dopamine (DA) signaling, with the hypofunctional variants (TaqIA-A1 allele, DRD2-141C Ins/Ins, DRD4 7-repeat, DAT1-10-repeat, Met/Met-COMT) receiving the lowest scores, and a composite score was calculated reflecting the total number of the five genotypes. Macronutrient intake during the Snack Test was the outcome. Results: Adjusting for z-score BMI at 48 months and sex, there was a significant interaction of the genetic profile and fetal growth on sugar intake [ β ˆ  = −4.56, p = 0.04], showing a positive association between the genetic score and sugar intake in IUGR children, and no association in non-IUGR children. No significant interactions were seen in other macronutrients. Conclusions: Variations in a genetic score reflecting DA signaling are associated with differences in sugar intake only in IUGR children, suggesting that DA function is involved in this behavioral feature in these children. This may have important implications for obesity prevention in this population.